Spiritual Resilience in Bereaved Young Women: A Case Study of a Young Woman Who Was Left to Die by Her Fiancé - Jajang Hartono; Ahmad Yunus (KEDJATI Journal of Islamic Civilization, 2025)
The grief of loss has been addressed in many studies. Most of these studies describe the grief of losing a husband or wife. Studies on the bereavement of a fiancé are few. This study aims to explore the role of spiritual resilience in the grieving process experienced by a young woman who was left by her fiancé. One of the issues they addressed was how people process their grief and assign meaning to the loss experience. This qualitative case study involved in-depth interviews to extract information about informants’ experiences and coping strategies. The results show that belief in destiny, social support from family and friends, and engagement in meaningful spiritual practices contribute significantly to developing spiritual resilience. The interpretation of the results of this analysis suggests that spiritual resilience not only helps individuals deal with grief but also promotes personal growth and emotional recovery. This research contributes to the field of Islamic psychology on the mechanisms of spiritual resilience in the recovery process from bereavement. Hence, this study provides insight for individuals and mental health practitioners who are facing similar issues.